Optically transparent polymer electrolyte films

JP2023554636A5Active Publication Date: 2024-12-19MATIV LUXEMBOURG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023537107
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-16
Filing Date
2021-12-14
Publication Date
2024-12-19
Estimated Expiration
2041-12-14

AI Technical Summary

Technical Problem

Existing electrolyte films for electrochromic windows suffer from poor optical clarity due to incompatibility between polymers and liquid electrolytes, which affects their suitability for smart window applications.

Method used

A formulation of electrolyte films incorporating organic carbonates and a second plasticizer material with a Hansen solubility parameter (Ra) of less than 5.0, preferably 3.79 or less, to enhance compatibility and transparency, using materials like diethyl carbonate, propylene carbonate, and dibenzoate or acrylic monomer to achieve sufficient conductivity and optical clarity.

Benefits of technology

The solution results in electrolyte films with improved optical transparency and ionic conductivity, suitable for electrochromic windows, achieving transmission greater than 80% and switching speeds of less than 1 minute.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Electrolyte films or cells for use in various applications, such as electrochromic windows, are provided. The electrolyte film includes a polymer layer, such as a thermoplastic polyurethane or polymethyl methacrylate, and an electrolyte within the polymer layer. The electrolyte includes a salt and a plasticizer. The plasticizer includes one or more materials selected to provide sufficient conductivity and optical transparency for operation of the electrolyte film in applications requiring substantial optical clarity and switching speed, such as smart windows.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This description relates to electrolyte films in general, and more specifically to electrolyte films used in electrochromic cells, such as those used in electrochromic windows. [Background technology]

[0002] Electrochromic windows, also known as smart windows, are a new technology for energy efficiency in buildings that controls the amount of sunlight passing through. They can also produce less glare than frit glass. Their efficiency depends on their placement, size, and weather, which affect the amount of sunlight exposure. Smart windows, which allow switching between light transmittance and reflectance, are rapidly gaining popularity. They are closely linked to the latest trends in sustainable, energy-efficient housing. Among the various possible technologies for smart windows, electrochromism is one of the most promising. Electrochromism is the phenomenon in which the color or opacity of a material changes in response to the application of voltage. The change in light transmittance properties in response to voltage allows for control of the amount of light and heat that passes through. Once the change is made, electricity is not required to maintain the particular shade achieved. In this way, electrochromic windows can block UV, IR, or certain wavelengths of visible light as needed.

[0003] The basic structure of an electrochromic device (ECD) typically embodies five layers stacked on a single substrate, or positioned as a laminated configuration between two substrates. In this structure, there are three main types of layered materials in the ECD: electrochromic (EC) layers, transparent conductive layers, and electrolytes. The EC layers conduct ions and electrons and belong to the category of mixed conductors. The electrolyte layer is a pure ionic conductor and separates the two EC layers. The transparent conductor is a pure electron conductor. Optical absorption occurs when electrons move from the transparent conductor into the EC layers, along with charge balance ions entering from the electrolyte. The ion-conducting layer can be a liquid, as seen in wet cell batteries. An example of such a liquid ion-conducting layer is propylene carbonate containing lithium perchlorate. One drawback of liquid electrolytes is that while they demonstrate acceptable ionic conductivity, they can leak from the ECD, posing a significant risk to the end user. To address this issue, the ion-conducting layer can be a polymer interlayer that remains solid under ambient conditions. Examples of such solid-phase ion-conducting layers are described in Ionic Conductivity of Polyether-Polyurethane Networks Containing Alkali Metal Salts. An Analysis of the Concentration Effect, Macromolecules, Vol. 17, No. 1, 1984, pgs. 63-66, to Killis, et al., and Poly(dimethylsiloxane)-Poly(ethylene oxide) Based Polyurethane Networks Used As Electrolytes in Lithium Electrochemical Solid State Batteries, Solid State Ionics, 15 (1985) 233-240, to Bouridah, et al., the entirety of the full disclosure is incorporated herein by reference for all purposes.

[0004] Solid polymer interlayer electrolytes eliminate the possibility of electrolyte leakage, but insufficient ionic conductivity becomes a problem. One solution to this problem is to combine the mechanical advantages of solid-phase electrolytes with the high ionic conductivity of liquid electrolytes by imbibing or plasticizing a liquid electrolyte into the polymer. For example, thermoplastic urethane polymers can be plasticized with propylene carbonate containing a lithium salt. This film can become solid under ambient conditions and have good mechanical strength. Furthermore, it can show a significant improvement in ionic conductivity compared to films containing untreated polymers with lithium salt additives. An example of this type of electrolyte is described in U.S. Patent No. 8,673,503, the full disclosure of which is incorporated herein by reference in whole for all purposes.

[0005] While films such as those mentioned above may function well in batteries or other applications, they are not optimized for smart windows because they are not sufficiently transparent. This is because the polymer and plasticizer are miscible with each other, meaning they do not completely dissolve in solution. For example, it was surprisingly discovered that an optical-grade polyether-based thermoplastic polyurethane polymer (i.e., Estane AG8451, manufactured by Lubrizol) plasticized with 43 phr propylene carbonate containing either 8.3% or 12.5% ​​w lithium perchlorate (LiClO4) exhibits significant haze under ambient conditions, yet the resulting film shows good mechanical properties. The loss of optical transparency due to the miscibility between the polymer and the liquid electrolyte renders such polymer electrolyte films of little value in electrochromic window applications. Therefore, what is needed is an improved formulation that can enable the incorporation of an electrolyte containing an organic carbonate into a polymer film without jeopardizing the optical clarity of the resulting electrolyte film. [Overview of the Initiative]

[0006] The following provides a simplified overview of the subject matter described in the claims in order to provide a basic understanding of some aspects of the subject matter described in the claims. This overview is not a comprehensive overview of the subject matter described in the claims. It is not intended to identify any important or crucial elements of the subject matter described in the claims, nor to detail the scope of the subject matter described in the claims. Its sole purpose is to present some of the concepts of the subject matter described in the claims in a simplified form, as an introduction to the more detailed descriptions that will be presented later. The present invention relates in general to electrolyte films, and more particularly to electrolyte films used in electrochromic cells, such as those used in electrochromic windows. In one embodiment, the electrolyte film comprises a polymer layer and an electrolyte within the polymer layer. The electrolyte comprises a salt and a plasticizer. The plasticizer comprises one or more materials selected to provide sufficient conductivity and light transmittance for the operation of the electrolyte film in applications requiring substantial light transmittance, such as smart windows. In certain embodiments, the plasticizer comprises one or more organic carbonates and a second plasticizer material embedded in the polymer layer with a salt. The organic carbonates and the second material are selected such that the Ra between the plasticizer and the polymer layer is less than about 5.0, preferably 3.79 or less. Ra is defined herein as the Hansen solubility parameter, which generally represents the overall compatibility of two materials that dissolve in each other and form a solution. The applicant has found that the Hansen solubility parameter is a reliable measure of the overall optical clarity of two or more cosolvents.

[0007] In certain embodiments, the plasticizer material is selected to have a haze of about 2% or less as measured by ASTM D1003-13. The applicant has also found that the plasticizer materials described herein have an Ra of about 3.79 or less for certain polymers that provide sufficient light transmittance for the operation of electrolyte films in desired applications such as smart windows. The organic carbonate and the second material have at least about 3.85 × 10 -5Siemens / cm, preferably about 3.85 × 10 -5 ~6×10 -4 It is also selected to provide ionic conductivity through an electrolyte film in the range of Siemens / cm. In certain embodiments, the organic carbonate is selected from the group consisting of diethyl carbonate, propylene carbonate, ethylene carbonate, gamma butrilolactone, dimethyl carbonate, methyl ethyl carbonate, glycerin carbonate, butylene carbonate, alkylene carbonate, and combinations thereof. In exemplary embodiments, the organic carbonate is selected from the group consisting of diethyl carbonate, propylene carbonate, and ethylene carbonate.

[0008] In one embodiment, the plasticizer comprises two or more organic carbonates, such as diethyl carbonate, propylene carbonate, or ethylene carbonate, which are mixed together. The applicant has found that a selected mixture of two or more such organic carbonates reduces the overall Ra between the plasticizer and the polymer, thereby increasing the optical clarity of the electrolyte film. In one such embodiment, the plasticizer comprises a mixture of diethyl carbonate and propylene carbonate that gives the electrolyte film sufficient conductivity and optical clarity. In an exemplary embodiment, the mixture contains about 40% to 90% by volume of propylene carbonate, more preferably about 50% to about 85% by volume of propylene carbonate, with the remainder being substantially diethyl carbonate.

[0009] In another embodiment, the second material is selected from the group consisting of dibenzoates, acrylate monomers, phthalates, aliphatic esters, nonaliphatic esters, ethylene glycol bis, trimellitates, sebacates, adipates, terephthalates, gluterates, glycers, azelates, maleates, epoxides, glycols, and polyethers, organic phosphates, alkyl citrates, glycerols, and acetylated monoglycerides, or mixtures thereof. In this embodiment, the plasticizer contains one of these materials in combination with an organic carbonate such as those described above. The applicant has found that a combination of one or more of these materials with an organic carbonate in a certain volume percentage reduces the overall Ra between the plasticizer and the polymer, thereby increasing the optical clarity of the electrolyte film. In preferred embodiments, the second material of the plasticizer comprises a dibenzoate or acrylic monomer. Thus, the plasticizer contains the organic carbonate and the dibenzoate or acrylic monomer in a relative volume percentage that gives the electrolyte film sufficient conductivity and optical clarity. In exemplary embodiments, the dibenzoate or acrylic monomer has a volume percentage between about 20% and about 80%, preferably between about 50% and 90%, with the remaining volume comprising the organic carbonate.

[0010] Suitable plasticizers, though not limited to: (1) propylene carbonate and dibenzoate, wherein the dibenzoate constitutes about 45% to about 95% by volume of the plasticizer; (2) ethylene carbonate and dibenzoate, wherein the dibenzoate constitutes about 55% to about 95% by volume of the plasticizer; (3) diethyl carbonate and dibenzoate, wherein the dibenzoate constitutes about 50% to about 95% by volume of the plasticizer; (4) ethylene carbonate and acrylic monomer, wherein the acrylic monomer constitutes about 48% to about 75% by volume of the plasticizer; (4) propylene carbonate and acrylic monomer, wherein the acrylic monomer constitutes about 33% to about 75% by volume of the plasticizer; (5) a mixture of 50% by volume of ethylene carbonate and 50% by volume of propylene carbonate, with dibenzoate (6) A combination of a material containing ethyl ester, in which the dibenzoate constitutes about 50% to about 95% by volume of the plasticizer; (7) A combination of a material containing dibenzoate, in which a mixture of 50% by volume of diethyl carbonate and 50% by volume of propylene carbonate constitutes about 5% to about 95% by volume of the plasticizer; (8) A combination of a material containing dibenzoate, in which a mixture of 33% by volume of diethyl carbonate and 66% by volume of propylene carbonate constitutes about 20% to about 95% by volume of the plasticizer; or (8) A combination of a material containing dibenzoate, in which a mixture of 66% by volume of diethyl carbonate and 33% by volume of propylene carbonate constitutes more than 0% to about 95% by volume of the plasticizer.

[0011] The polymer layer may contain any suitable polymer that provides sufficient transmittance to visible light and exhibits appropriate adhesion to other surfaces of the electrochromic film that the polymer may come into contact with. Suitable polymers include thermoplastic polymers or acrylic polymers, such as polymethyl methacrylate (PMMA). In preferred embodiments, the polymer includes a thermoplastic polymer such as thermoplastic polyurethane (TPU). In exemplary embodiments, the polymer includes an aliphatic thermoplastic polyurethane having a durometer of about 70 Shore A to about 80 Shore D. The salts preferably include alkali or alkaline earth metal salts, such as lithium salts, or salts having the elements Na, K, Cs, Mg, and Ag as cations. Suitable lithium salts include: LiCl, LiF, LiI, LiNO3, LiClO4, LiBF4, LiPF6, LiAsF6, lithium triflate, lithium imide, LiTFSI, LiTDI, and the like. In another embodiment, the electrochromic cell comprises first and second layers of an optically transparent material, such as glass or other suitable material, and an ion-conducting layer between the first and second layers. The ion-conducting layer comprises a polymer layer, a salt, and a plasticizer. The plasticizer is selected such that the Ra between the plasticizer and the thermoplastic polymer layer is less than 5, preferably less than 3.79.

[0012] The electrochromic cell may further include first and second electrochromic layers disposed between first and second layers of optically transparent material and an ion-conducting layer. The cell may further include a layer of transparent conductive oxide between each of the first and second layers of optically transparent material and the first and second electrochromic layers. In another embodiment, a window is provided which includes an electrochromic cell such as those described above. The window has a transmittance greater than about 80%, preferably greater than about 85%, and a switching speed in the range of less than 1 minute, preferably less than 30 seconds. The enumeration herein of desired objectives that can be satisfied by various embodiments of the description of the present invention does not imply or suggest that any or all of these objectives, individually or collectively, are given as essential features in any of the most general embodiments or more specific embodiments thereof of the description of the present invention. [Brief explanation of the drawing]

[0013] [Figure 1] This is a schematic diagram of an electrochromic cell for windows. [Figure 2A-C] This graph shows the Ra of TPU for various formulations described herein. [Modes for carrying out the invention]

[0014] This description and accompanying drawings illustrate exemplary embodiments and should not be construed as limiting, and the claims define the scope of the invention, including its equivalents. Various mechanical, compositional, structural, and operational modifications may be made without departing from the scope of the claims, including the description and equivalents of the invention. In some cases, well-known structures and techniques are not shown or described in detail so as not to obscure the above description. Similar numbers in two or more figures represent the same or similar elements. Furthermore, elements and their related aspects that are detailed in relation to one embodiment may be included in other embodiments that are not specifically illustrated or described, whenever practical. For example, if an element is detailed with reference to one embodiment or not described with reference to a second embodiment, the element may nevertheless be included in the second embodiment and described in the claims. Furthermore, the descriptions herein are for illustrative purposes only and do not necessarily reflect the actual shape, size, or dimensions of the system or the exemplary components. It should be noted that, as used herein and in the appended claims, the use of the singular forms “a,” “an,” and “the,” and any singular form of any word, includes multiple referents unless it is clearly and undeniably limited to one referent. The term “includes” as used herein and its grammatical variations are intended to be non-restrictive, and therefore the enumeration of items in a list does not exclude other similar items that may be substituted or added to the enumerated items.

[0015] Unless otherwise noted, any quantitative values ​​are approximations, whether or not they are described as "about," "approximately," or similar. The materials, methods, and examples described herein are illustrative and not intended to be limiting. Any molecular weight or molecular mass values ​​are approximations and are given for illustrative purposes only. The following description is presented with respect to electrochromic devices or ECDs for windows, but it should be understood that the devices and methods disclosed herein can be readily adapted for use in a variety of other applications, such as mirrors, optical shutters, color-changing eyeglasses, welding visors, aircraft windows, display devices, electrochromic glazing systems, safety laminated glass screens for automobiles and the like, dynamically coloring goggles, readable displays, helmet visors, paper for stylus drawing, and other devices that can change their optical properties, or more generally, change their electromagnetic transmittance as a result of an applied potential.

[0016] Typically, ECDs come in two types, depending on the device's operating mode, namely transmission mode and reflection mode. In transmission mode, the conductive electrodes are transparent, and the intensity of light passing through them is controlled; this mode is typically used in smart window applications. In reflection mode, one of the transparent conductive electrodes (TCEs) is replaced with a reflective surface such as aluminum, gold, or silver, and the intensity of reflected light is controlled; this mode is useful in car rearview mirrors and EC display devices. Electrochromic devices can also be classified into two types according to the type of electrolyte used. The laminated ECD incorporates a liquid gel, while the solid electrolyte ECD incorporates a solid inorganic or organic material. The basic structure of an electrochromic device is embodied as five stacked layers on one substrate or positioned between two substrates with a laminated structure.

[0017] An ECD typically includes five layers positioned between two substrates such as glass or flexible polyester foil. The central part of the device is an ion conductor called an electrolyte that ensures ion exchange between two electrode materials. By applying an electric field, one of the electroactive materials is reduced, while the other material is oxidized, leading to a change in the color or opacity of at least one of those materials, inducing a change in coloration or opacity throughout the ECD device. Referring now to FIG. 1, a representative electrochromic window 100 includes first and second optically transparent layers 102, 104 and an ion conducting layer 106 therebetween. The optically transparent layers 102, 104 may include a suitably transparent material that will depend on the particular application of the window 100. In an exemplary embodiment, the layers 102, 104 include glass such as toughened glass, laminated glass, etched glass, etc. Of course, there are other substantially transparent materials that can be used as the layers 102, 104, such as ceramic or polymer materials, for example, acrylic, polyethylene terephthalate (PET), polycarbonate, or polyphosphonate substrates.

[0018] In certain embodiments, cell 100 further includes first and second electrochromic layers 108, 116. The electrochromic or EC layers 108, 116 conduct ions and electrons and belong to the type of mixed conductors. The electrochromic layers 108, 116 may include transition metal oxides, transition metal complexes, conducting polymers, viologens, polyaniline, polythiophene, WO3, Prussian blue, and combinations thereof. In some embodiments, the first electrochromic layer 108 is a cathode electrochromic conducting polymer such as PEDOT, PProDOT, PEDOP, PTT, PAEM-EDOT, and combinations thereof. The second electrochromic layer 110 may include anode electrochromic conducting polymers such as poly(BEDOT-NMCz), PPro-NPrS, and derivatives and combinations thereof. In certain embodiments, cell 100 further includes transparent oxide layers 112, 114 between the transparent layers 102, 104 and the electrochromic layers 108, 116. The transparent oxide layers 112, 114 are pure electron conductors and may include any suitable material having relatively low light absorption such as indium oxide, silicon oxide, indium tin oxide, zinc oxide, or combinations thereof. These metal oxides may also be doped with trace amounts of fluoride, antimony, or aluminum to improve conductivity. Other transparent conductive materials such as electrochromic conducting polymers, for example PEDOT / PSS or carbon nanotube coatings, may be used.

[0019] The ion conducting layer 106 includes a polymer layer and an electrolyte. The electrolyte includes a salt and a plasticizer and may be solid, liquid, or gel. In preferred embodiments, the salt is plasticized or, if not, embedded within the polymer layer by an organic solvent to form a liquid or gel electrolyte. The salt may be present at about 1 to about 8 wt%, the polymer may be present at about 20 to about 70 wt%, and the remainder includes a plasticizing solvent. In preferred embodiments, the electrolyte takes the form of a film. The thickness of the film is selected according to the desired application. In window and similar applications, the thickness is selected to provide both the conductivity essential for the operation of the electrochromic cell and the light transmittance required for the window. For example, the film may have a thickness of 1 to 125 μm, preferably about 25 to about 125 μm, and more preferably about 30 to about 70 μm. In certain embodiments, the polymer, salt, and plasticizer may be dissolved in a precursor material such as tetrahydrofuran (THF) or oxolane, or a similar type of precursor. The applicant has found that by using coating chemistry, even thinner films can be produced, thereby increasing the ionic conductivity of the films.

[0020] The electrolyte components will be selected to provide sufficient light transmittance and ionic conductivity for the desired application. With respect to ionic conductivity, the “switching speed” of the electrochromic device is the time required for the electrochromic device to change its optical density from a completely decolorized state to a completely colored state. In certain applications, such as smart windows, the optimal switching speed for the device is in the range of less than one minute, preferably less than 30 seconds. To satisfy the switching speed requirements of the electrochromic device, the electrolyte must have sufficient ionic conductivity. The electrolyte components must ensure that the ionic conductivity of the ion-conducting layer 106 is at least approximately 3.85 × 10⁻⁶. -5 Siemens / cm, preferably about 3.85 × 10 -5 ~Approx. 6×10 -4 The conductivity is selected to be between Siemens / cm, but the ionic conductivity is 6 × 10 in certain application examples. -4 It should be understood that values ​​greater than Siemens / cm are acceptable. Transmittance refers to the ratio of the radiant power transmitted through a material or device to the incident radiant power. Transmittance is usually expressed as a percentage. For example, an electrochromic device with a transmittance of 50% (at a particular wavelength) will absorb half of the incident light and pass the other half through. Here, the components are selected such that the transmittance of the ECD is at least greater than about 80%, preferably greater than about 85%.

[0021] The light transmittance of an ECD can also be evaluated based on the "haze" observed when light passes through the ECD. The haze is measured using a haze meter, which typically includes a fiber optic spectrometer, a light source with integrated optical amplification and parallelization lenses, and a custom haze measuring sphere with a diffuse transmission port and sample clip. Electrolytes were measured under the standard test method for haze (ASTM D1003-13). The electrolyte composition was selected so that the haze was 2% or less. The performance of electrochromic devices can be evaluated in terms of switching time and transmittance (or transmittance contrast) under various humidity and temperature conditions. These devices may also be tested under reduced pressure. The cycle voltage for operating the cell may be determined by cyclically operating the cell at various voltages and by monitoring the change in T% in the transparent state after several cycles. Potential cycling or step operation can be used to identify a preferred device voltage with respect to the desired operating life.

[0022] All components of the electrolyte form a homogeneous, generally colorless, and extremely transparent composition. The conductive salts dissolve completely in the polymer. The materials for ECDs are also selected to obtain sufficient extrudeability so that the materials can be extruded together to form the final ECD device. Extrudeability is the force required to push or forcibly push an object through an extruder, such as a single-screw or twin-screw extruder that rotates simultaneously or in opposite directions, or a twin-screw compounder with tightly meshing parts. The average extruder force for one or more materials can be tested under standard methods of applying force to the material until it flows through one (or more) outlets, which may take the form of one or more slots or holes. The material is compressed until the structure of the product collapses and is extruded through the outlet. The applicant has determined that higher levels of plasticizer can adversely affect both the ionic conductivity and extrudeability of the liquid plasticizer and polymer. Therefore, the materials selected herein provide sufficient light transmittance as well as conductivity and extrudeability.

[0023] The polymer layer may contain any suitable polymer that provides sufficient transmittance to visible light and exhibits appropriate adhesion to surfaces that the polymer may come into contact with within the electrochromic cell. Suitable polymers include thermoplastic polymers or acrylic polymers, such as polymethyl methacrylate (PMMA). In certain embodiments, the polymer crosslinks sufficiently in the presence of a solvent to form a gel. In preferred embodiments, the polymer includes a thermoplastic polymer such as thermoplastic polyurethane (TPU). In exemplary embodiments, the polymer includes an aliphatic thermoplastic polyurethane having a durometer of at least about 70 Shore A to about 80 Shore D. Naturally, those skilled in the art should understand that other polymer materials can be used. For example, polyolefins, polyesters, or polycaprolactones, such as polyethylene terephthalate or polybutylene terephthalate, are also considered suitable. Alternatively, thermosetting polymers, irreversibly cured by curing from soft solid or viscous liquid prepolymers, may be used in combination with thermoplastic polymers.

[0024] The electrolyte film may contain a mixture of two or more different polymers, or two or more different polymer layers. In the former case, the molecular weight of the polymers can be selected according to the desired properties of the electrolyte. The electrolyte film may contain fillers having particle sizes ranging from approximately 1 nm to approximately 20 μm. The fillers should have a light transmittance higher than 80% when measured with respect to the pure material. Suitable possible fillers include polymer particles such as polystyrene, polycarbonate, or polymethyl methacrylate. Oriented fillers, such as glass powder, glass nanoparticles, or inorganic oxides, and mixed oxides are also suitable.

[0025] The salts preferably include alkali or alkaline earth metal salts, such as lithium salts, lithium halides, lithium-metal salts, and other lithium compounds. Suitable lithium salts include LiCl, LiF, LiI, LiNO3, LiClO4, LiBF4, LiPF6, LiAsF6, lithium triflate, lithium perchlorate, lithium imide, LiTFSI, LiTDI, and the like. In certain embodiments, the lithium salt is present in an amount of about 1 to 40% by mass, preferably between about 2 and about 10% by mass. Naturally, it should be understood that other salts may be used, such as those containing the elements Na, K, Cs, Mg, and Ag as cations. Organic salts such as sodium octyl sulfate and sodium dodecylbenzene sulfate can also be used. It is also possible to use a mixture of two or more conductive salts.

[0026] In certain embodiments, an ionic liquid additive may be included in the formulation to enhance the plasticizer's noionic conductivity. The ionic liquid additive may be readily miscible with one or more of the plasticizers described herein, and may preferably be a liquid at room temperature. Non-limiting examples of such ionic liquids include, but are not limited to, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([PYR14][TFSI]), 1-ethyl-3-methylimidazolium, bis[(trifluoromethyl)sulfonyl]imide ([C2mim][TFSI]), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide ([C2mim][FSI]), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (C4mim][TFSI]), and 1-butyl-3-methylimidazolium bis(fluorosulfonyl)imide (C4mim][FSI], and mixtures thereof. In other embodiments, a new class of nanomaterials may be included in the formulation to increase ionic conductivity and / or mechanical strength. These are solids that do not dissociate when added to plasticizers. They can be incorporated via mechanical homogenization techniques, including but not limited to high-intensity stirring, sonication, dry or wet milling, and surfactant-assisted wet milling. Examples of such nanomaterials include, but are not limited to, SiO2, ZrO2, Al2O3, and LiLaTiO3.

[0027] The plasticizer preferably comprises at least one organic solvent, such as a carbonate solvent or a lactone solvent. The organic solvent should be selected from materials that provide sufficient ionic conductivity to obtain a suitable switching rate with respect to the window. Suitable lactone solvents include, but are not limited to, propiolactone, butyrolactone, crotonolactone, valerolactone, and mixtures thereof. Suitable carbonate solvents include diethyl carbonate, propylene carbonate, ethylene carbonate, gammabutyrolactone, dimethyl carbonate, methylethyl carbonate, glycerin carbonate, butylene carbonate, alkylene carbonate, and combinations thereof. In certain embodiments, the carbonate solvent includes diethyl carbonate, propylene carbonate, ethylene carbonate, and combinations thereof. The plasticizer will comprise at least one carbon-based solvent and one other plasticizing material that increases the light transmittance of the electrolyte. In some embodiments, the plasticizer is another organic carbonate, such as diethyl carbonate, propylene carbonate, or ethylene carbonate. The applicant has found that a selected mixture of two or more such organic carbonates reduces the overall Ra between the plasticizer and the polymer, thereby increasing the optical transparency of the electrolyte film. In one such embodiment, the plasticizer comprises a mixture of diethyl carbonate and propylene carbonate, giving the electrolyte film sufficient conductivity and optical transparency. In an exemplary embodiment, the mixture contains about 40% to 90% by volume of propylene carbonate, more preferably about 50% to about 85% by volume, with the remainder of the mixture substantially comprising diethyl carbonate.

[0028] In another embodiment, the plasticizer is selected from the group consisting of dibenzoates, acrylate monomers, phthalates, aliphatic esters, nonaliphatic esters, ethylene glycol bis, trimellitates, sebacates, adipates, terephthalates, glutarates, glycerides, azelates, maleates, epoxide-modified soybean oil, glycols, and polyethers, but not limited to triethylene glycol dihexanoate (3G6), tetraethylene glycol diheptanoate (4G7), triethylene glycol bis(2-ethylhexanoate) (TEG-EH), tetraethylene glycol bis(2-ethylhexanoate) (4GEH), and polyethylene glycol bis(2-ethylhexanoate) (PEG-EH), organic phosphates, but not limited to tricresyl phosphate (TCP) and tributyl phosphate (TBP), alkyl citrates, glycerols, and acetylated monoglycerides, or mixtures of any of these materials. In this embodiment, the plasticizer contains one of these materials in combination with an organic carbonate, such as those described above. The applicant has found that a certain volume percentage combination of an organic carbonate and one or more of these plasticizers reduces the overall Ra between the solvent and the polymer, thereby increasing the optical transparency of the electrolyte film.

[0029] Other plasticizers may be included, such as esters of organic acids, e.g., esters of adipic acid or phthalic acid; esters of inorganic acids, e.g., esters of boric acid, carbonic acid, sulfuric acid, and phosphoric acid. Ethers such as dibutyl ether, dihexyl ether, and diheptyl ether may also be included. Various mixtures of plasticizers may be used, provided that the resulting mixture imparts light transmittance and sufficient conductivity to the electrolyte described herein. The plasticizer is usually present in an amount of 1 to 90% by mass, preferably about 30% to about 90% by mass. In certain embodiments, the plasticizer comprises a dibenzoate or an acrylic monomer. The solvent may include an organic carbonate and a plasticizer that includes a dibenzoate or an acrylic monomer that provides sufficient conductivity and optical transparency to an electrolyte film for a desired application such as a window. In an exemplary embodiment, the plasticizer has a volume percentage between about 20% and about 80% of the mixture, preferably between about 50% and 90%.

[0030] The compatibility between TPU and the liquid electrolyte was evaluated based on their Hansen solubility parameters. These parameters were obtained from HSPiP version 5.3.04 software. Hansen solubility parameters are used to predict whether one material will dissolve in another. Each molecule is given three parameters - δD, δP, and δH. δD represents the energy from the intermolecular dispersion forces. δP represents the energy from the intermolecular dipole-dipole forces, and ∂H represents the energy from the intermolecular hydrogen bonds. The distance (Ra) between the Hansen parameters of species 1 and 2 in Hansen space is calculated according to Equation 1 below. Equation 1 Ra 2 = 4(δD2 - δD1) 2 +(δP2 - δP1) 2 +(δH2 - δH1) 2 ... The Hansen parameters for several organic carbonates and other co-solvents are listed in Table 1 below.

[0031]

Table 1

[0032] The applicant tested the clarity of an electrolyte containing TPU, lithium salt, and propylene carbonate (Ra = 9.5, as shown in Table 1). This test was carried out in the following steps: (1) Dissolve LiClO4 in propylene carbonate, then add Bravender; (2) Dry about 250 g of AG8451 overnight; (3) Set the process temperature to 115°C; (4) Add AG8451 to a mixer and run at 25 RPM; (5) Once AG451 has dissolved (about 20 minutes), add LE dropwise with a syringe and increase the mixer speed to 200 rpm to achieve a torque of 1000 m-g. (6) Reduce the mixer speed to 60 rpm with a torque of 1000 m-g to lower and stabilize the melting temperature; (7) Once the melting temperature is stabilized, maintain at 60 RPM for a minimum of 15 minutes or until homogenized; (8) Flatten the compound as much as possible, let it cool, and then package it in a Ziploc bag; (9) Press the 20-mil sheet between two PET films at 115°C; and (10) Package it in a Ziploc bag with a desiccant. The applicant's tests showed that this composition made the electrolyte optically opaque (i.e., haze greater than 2% when measured by ASTM D1003-13).

[0033] The applicant also tested the transparency of an electrolyte containing TPU, lithium salt, and Benzoflex 9-88. Similar test methods were used. These tests showed that the composition was an optically transparent electrolyte (i.e., haze of less than 2% as measured by ASTM D1003-13). Since the Ra of Benzoflex 9-88 and TPU is 3.79, this value was selected as a proxy threshold for determining the optical transparency of the plasticized TPU film. In other words, Ra < 3.79 is more likely to produce an optically transparent film, while Ra > 3.79 is more likely to produce an optically opaque film. However, it should be understood that the description of the present invention is not necessarily limited to cosolvents having an Ra of 3.79 or less. The applicant determined that an Ra of 3.79 or less would result in an optically clear ECD with a haze of 2% or less. However, the Ra between cosolvents can be higher than 3.79 and may still result in a sufficiently clear device depending on the specific application of the ECD. In certain embodiments, for example, the Ra between cosolvents may be about 5.0 or less. The Ra values ​​of mixed plasticizers versus TPU are calculated using Equation 1. These are plotted in Figures 2A–2C for several systems. For each plotted line in the graphs of Figures 2A–2C, the left end of the line represents 0% of the first solvent and 100% of the second solvent, as listed in the legend above the graph. Similarly, the right end of the line represents 100% of the first solvent and 0% of the second solvent. For example, B988+EC starts on the left side of the graph in Figure 2A with an Ra of 12.41 for TPU (100 vol% ethylene carbonate or EC) and ends on the right side of the graph with an Ra of 3.79 for TPU (100 vol% Benzoflex 9-88 SG or B988). The line marked "Optical Transparency Threshold" represents 100% B988 or an Ra of 3.79 for reference purposes.

[0034] It is interesting to note that the Ra values ​​of each mixed electrolyte system shown in Figures 2A-2C pass through the minimum value. In other words, the compatibility of a mixed electrolyte system with TPU can be better than that of individual electrolytes having the same TPU at a certain volume percentage of the mixed plasticizer. This observation can be advantageously used to incorporate organic carbonates into plasticizer mixtures without exceeding the Ra threshold of 3.79 described in the previous paragraph. For example, a 50 / 50 volume blend of Benzoflex 9-88 and propylene carbonate has the same Ra for TPU as 100 volume% Benzoflex 9-88. Therefore, a 50 / 50v blend of Benzoflex 9-88 and propylene carbonate should have the same compatibility with TPU as 100%v Benzoflex 9-88. Similarly, a 50 / 50v blend of propylene carbonate and diethyl carbonate has the same Ra to TPU and therefore the same compatibility as 100%v Benzoflex 9-88. A 33 / 66v blend of diethyl carbonate and propylene carbonate has a lower Ra to TPU and therefore superior compatibility compared to 100%v Benzoflex 9-88.

[0035] Figures 2A–2C show several volume percentage combinations of organic carbonates and other cosolvents that can impart sufficient permeability to ECD according to the parameters defined herein. For example, one such combination includes Benzoflex 9-88 SG and ethylene carbonate (see Figure 2A). Approximately 55%–100% volume percentage of Benzoflex 9-88 G (with the remainder of the solvent being ethylene carbonate) produces a plasticizer with an Ra of 3.79 or less relative to TPU. To further refine these parameters, the total conductivity of the resulting electrolyte is tested according to the test methods discussed above. It is understood that at least some volume percentage of ethylene carbonate is required in the mixture to bring satisfactory conductivity to the electrolyte (i.e., 100% Benzoflex 9-88 G is not considered sufficiently conductive). Therefore, the volume percentage that satisfies both the transparency and conductivity requirements is Benzoflex 9-88 G between approximately 55% and 90%, preferably between approximately 55% and 75%, with the remainder of the solvent comprising ethylene carbonate.

[0036] As another example, propylene carbonate can be combined with SR355 to produce an optically transparent film. As shown in Figure 2A, a volume percentage of approximately 33% to 75% SR355 (the remainder being propylene carbonate) produces a combined plasticizer with an Ra of 3.79 or less relative to the TPU. Therefore, even though each of these plasticizers may be optically opaque to the TPU on its own, the combination of the two materials in this volume range is considered to give an optically transparent electrolyte with a haze of 2% or less.

[0037] Other suitable combinations of organic carbonates and other cosolvents shown in Figures 2A and 2B include, but are not limited to, the following: (1) a mixture of Benzoflex 9-88 SG and propylene carbonate containing about 45% to about 95% Benzoflex 9-88 G (preferably 90% or less of the desired conductivity) and the remainder of the solvent being propylene carbonate; (2) a mixture of Benzoflex 9-88 SG and diethyl carbonate containing about 50% to about 95% Benzoflex 9-88 G (preferably 90% or less of the desired conductivity) and the remainder of the solvent being diethyl carbonate; (3) a mixture of SR355 and ethylene carbonate containing about 48% to about 75% SR355 and the remainder of the solvent being ethylene carbonate; (4) Benzoflex 9-88 (5) A mixture of SG and a 50 / 50 mixture of propylene carbonate and ethylene carbonate, comprising about 50% to about 95% Benzoflex 9-88 G (preferably 90% or less of the target conductivity) and the remainder of the solvent comprising a 50 / 50 mixture of ethylene carbonate and propylene carbonate; (6) A mixture of Benzoflex 9-88 SG and a 50 / 50 mixture of propylene carbonate and diethyl carbonate, comprising about 5% to about 95% Benzoflex 9-88 G (preferably 90% or less of the target conductivity) and the remainder of the solvent comprising a 50 / 50 mixture of diethyl carbonate and propylene carbonate; (7) A mixture of Benzoflex 9-88 SG and 66 / 33 polyethylene carbonate and diethyl carbonate, comprising about 20% to about 95% Benzoflex 9-88 A mixture comprising G (preferably 90% or less of the desired conductivity) and the remainder of the solvent comprising a 66 / 33 mixture of propylene carbonate and diethyl carbonate;Or (7) a mixture of Benzoflex 9-88 SG and a 33 / 66 mixture of propylene carbonate and diethyl carbonate, comprising Benzoflex 9-88 G in amounts from about 0% to about 95% (preferably 90% or less of the desired conductivity) and the remainder of the solvent comprising a 33 / 66 mixture of propylene carbonate and diethyl carbonate.

[0038] It should also be noted that by combining two types of carbonates, it is possible to obtain an Ra of 3.79 or less for TPU in selected volume combinations. For example, as shown in Figure 2B, a mixture of ethylene carbonate and diethylene carbonate has an Ra of less than 3.79 when the volume percentage of diethyl carbonate is approximately 50% to 85% and the remainder is ethylene carbonate. The results in Figures 2A-2C are for illustrative purposes only and are not intended to be exhaustive. Those skilled in the art should be able to select other organic carbonates and cosolvents such that the Ra for TPU is 3.79 or less. Examples of cosolvents, though not limited to, may include other dibenzoate plasticizers, e.g., Benzoflex 352, Benzoflex 2088, Benzoflex 50, etc.; other phthalate plasticizers, e.g., diisobutyl phthalate, diisononyl phthalate, etc.; other non-phthalate plasticizers, e.g., 1,2-cyclohexanedicarboxylic acid diisononyl ester (DINCH); and other non-aromatic plasticizers, e.g., triethylene glycol bis(2-ethylhexanoate) (TEG-EH), tetraethylene glycol bis(2-ethylhexanoate), polyethylene glycol bis(2-ethylhexanoate) (PEG-EH), etc.

[0039] The mixed plasticizer may preferably contain, but is not limited to, one or more additives such as UV stabilizers or blockers, e.g., Uvinul® or Irgastab®, antioxidants, e.g., Irganox® or Sicstab®, viscosity modifiers, dispersion aids, and photoinitiators. The electrolyte can be prepared by plasticizing the above components and intensively mixing them with other components at high temperature in a suitable mixer. A suitable intensive mixer is a compounding machine or a single-screw or multi-screw extruder. Extrusion devices that can be used include, for example, single-screw and twin-screw machines, and tightly meshing twin-screw compounding machines rotating in the same direction or in opposite directions. The electrolyte may be formed into a film using a melting pump, slot die, and a suitable smoothing tool, such as a chill roll polishing stack. The film can then be processed by further process steps, for example, by a rolling calender or chill roll method. Furthermore, a surface structure can be embossed onto the film during this process. In certain embodiments, the plasticizer can be blended with the TPU via a molten blend. The TPU can be pre-mixed with the plasticizer before being fed into a single-screw or twin-screw extruder equipped with a flat die. Alternatively, the dry TPU and the plasticizer (powder, granules, pellets, etc.) can be fed separately into a twin-screw compounding extruder. [Examples]

[0040] (Example 1) Estane AG8451 optical-grade polyether TPU was treated with a 43 phr 50 / 50 w Benzoflex 9-88 / propylene carbonate mixed plasticizer containing 0.4 M LiClO4. LiClO4 was dissolved in propylene carbonate, then mixed with the plasticizer and dried overnight. In two separate tests, the LiClO4 / PC mass ratio was between approximately 8% and 13%. The material was placed in a twin-screw plasticizer mixer, the TPU was pre-melted at 115°C, mixed at 25 RPM, and then the mixed plasticizer liquid electrolyte was slowly added by syringe. The molten material was homogenized for a minimum of 15 minutes. Once AG8451 had melted (approximately 20 minutes), LE was added dropwise by syringe. The mixer speed was increased to 200 rpm until a torque of 1000 m-g was achieved. At a torque of 1000 m-g, the mixer speed was reduced to 60 rpm, and the melting temperature was lowered to stabilize the process. Once the melting temperature stabilized, the shaft was maintained at 60 RPM for a minimum of 15 minutes or until the mixture was homogenized. The compound was flattened as much as possible and cooled. It was then packaged in a Ziploc bag. A 20 mil sheet was pressed between two PET films and then packaged in a Ziploc bag with a desiccant.

[0041] A film was cast from this material via compression molding using a Carver press machine at 230°F to produce an optically transparent 10 mil electrolyte film under ambient conditions. The film was laminated separately with one cathode and two anode samples. The resulting laminates were also optically transparent 5 hours after vacuum lamination. Devices, systems, and methods have been described herein in detail according to certain preferred embodiments thereof, but those skilled in the art may make many modifications and changes thereto. Therefore, the foregoing description should not be construed as limiting, but rather as being limited only by the spirit and scope of the following claims, including such obvious modifications described herein.

Claims

1. A polymer layer, An electrolyte in the polymer layer, the electrolyte comprising a salt and a plasticizer. Including, the Ra between the plasticizer and the polymer layer is less than about 5; Electrolyte film.

2. 2. The film of claim 1, wherein the Ra is 3.79 or less.

3. 10. The film of claim 1, wherein the film comprises a haze of about 2% or less as measured by ASTM D1003-13.

4. The film has a thickness of at least about 3.85×10 -5 10. The film of claim 1 having an ionic conductivity of Siemens / cm.

5. The film of claim 1 , wherein the plasticizer comprises a mixture of propylene carbonate and diethyl carbonate.

6. The film of claim 5, wherein the propylene carbonate has a volume percentage of the mixture of about 50% to about 85%.

7. 2. The film of claim 1, wherein the plasticizer comprises an organic carbonate and a second material selected from the group consisting of dibenzoates, acrylate monomers, phthalates, aliphatic esters, non-aliphatic esters, ethylene glycol bis, trimellitates, sebacates, adipates, terephthalates, gluterates, glycerides, azelates, maleates, epoxidized soybean oil, glycols and polyethers, organic phosphates, alkyl citrates, glycerol and acetylated monoglycerides, or mixtures thereof.

8. The film of claim 7, wherein the second material has a volume percentage of the plasticizer of about 20% to about 80%.

9. 8. The film of claim 7, wherein the organic carbonate is selected from the group consisting of diethyl carbonate, propylene carbonate, ethylene carbonate, gamma butyrolactone, dimethyl carbonate, methyl ethyl carbonate, glycerin carbonate, butylene carbonate, alkylene carbonate, and combinations thereof.

10. 8. The film of claim 7, wherein the organic carbonate is selected from the group consisting of diethyl carbonate, propylene carbonate, and ethylene carbonate.

11. 8. The film of claim 7, wherein the second material is selected from the group consisting of dibenzoate plasticizers and acrylic monomers.

12. A polymer layer, An electrolyte in the polymer layer, the electrolyte comprising a salt and a plasticizer. Including, A haze of 2% or less as measured by ASTM D1003-13 and a viscosity of at least about 3.85×10 -5 and an ionic conductivity in Siemens / cm.

13. 13. The electrolyte film of claim 12, wherein the plasticizer comprises a carbonate solvent selected from the group consisting of propylene carbonate, diethyl carbonate, and ethylene carbonate.

14. 13. The electrolyte film of claim 12, wherein the plasticizer comprises a mixture of propylene carbonate and diethyl carbonate.

15. 14. The electrolyte film of claim 13, wherein the plasticizer further comprises a material selected from the group consisting of dibenzoates, acrylate monomers, phthalates, aliphatic esters, non-aliphatic esters, ethylene glycol bis, trimellitates, sebacates, adipates, terephthalates, gluterates, glycerides, azelates, maleates, epoxidized soybean oil, glycols and polyethers, organic phosphates, alkyl citrates, glycerol and acetylated monoglycerides, or mixtures thereof.

16. 13. The electrolyte film of claim 12, wherein the polymer layer comprises a thermoplastic polyurethane, and the Ra between the thermoplastic polyurethane and the plasticizer is about 3.79 or less.

17. A polymer layer, An electrolyte in the polymer layer, the electrolyte comprising a salt and a plasticizer. Including, the plasticizer comprises an organic carbonate and a material selected from the group consisting of dibenzoates, acrylate monomers, phthalates, aliphatic esters, non-aliphatic esters, ethylene glycol bis, trimellitates, sebacates, adipates, terephthalates, gluterates, glycerides, azelates, maleates, epoxidized soybean oil, glycols and polyethers, organic phosphates, alkyl citrates, glycerol and acetylated monoglycerides, or mixtures thereof; Electrolyte film.

18. 18. The film of claim 17 or 18, wherein the organic carbonate comprises propylene carbonate, the material comprises a dibenzoate, and the dibenzoate comprises about 45% to about 95% by volume of the plasticizer.

19. 18. The film of claim 17 or 18, wherein the organic carbonate comprises ethylene carbonate, the material comprises a dibenzoate, and the dibenzoate comprises about 55% to about 95% by volume of the plasticizer.

20. 18. The film of claim 17 or 18, wherein the organic carbonate comprises diethyl carbonate, the material comprises a dibenzoate, and the dibenzoate comprises about 50% to about 95% by volume of the plasticizer.

21. 18. The film of claim 17 or 7, wherein the organic carbonate comprises ethylene carbonate, the material comprises an acrylic monomer, and the acrylic monomer comprises about 48% to about 75% by volume of the plasticizer.

22. 18. The film of claim 17 or 7, wherein the organic carbonate comprises propylene carbonate, the material comprises an acrylic monomer, and the acrylic monomer comprises about 33% to about 75% by volume of the plasticizer.

23. 18. The film of claim 17 or 7, wherein the organic carbonate comprises a mixture of 50% by volume ethylene carbonate and 50% by volume propylene carbonate in combination with the material, the material comprising a dibenzoate, the dibenzoate comprising from about 50% to about 95% by volume of the plasticizer.

24. 18. The film of claim 17 or 7, wherein the organic carbonate comprises a mixture of 50% by volume diethyl carbonate and 50% by volume propylene carbonate in combination with the material, the material comprising a dibenzoate, the dibenzoate comprising from about 5% to about 95% by volume of the plasticizer.

25. 18. The film of claim 17 or 7, wherein the organic carbonate comprises a mixture of 33 volume percent diethyl carbonate and 66 volume percent propylene carbonate in combination with the material, the material comprising a dibenzoate, the dibenzoate comprising from about 20 volume percent to about 95 volume percent of the plasticizer.

26. 18. The film of claim 17 or 7, wherein the organic carbonate comprises a mixture of 66% by volume diethyl carbonate and 33% by volume propylene carbonate in combination with the material, the material comprising a dibenzoate, the dibenzoate comprising from greater than 0% to about 95% by volume of the plasticizer.